PERAN BADAN KEHORMATAN DALAM MENJAGA KEDISIPLINAN KEHADIRAN ANGGOTA DPRD KOTA SERANG (STUDI TENTANG MEKANISME ETIK DAN KEPATUHAN PADA RAPAT PARIPURNA) - Wahyudi, Amelinda Kusbandiah; Arasid, Mohamad Ikrom; Rahayu, Luis Fiska; Widodo, Wahyu; Arifin, Suherman (Gapenas Publisher, 2025)
This study aims to understand the role of the Honorary Council (BK) of the Regional House of Representatives (DPRD) of Serang City in maintaining the disciplinary attendance of council members, particularly in the context of plenary meetings. The background of this research stems from the significance of attendance as part of the accountability and integrity of legislative institutions. This research employs a descriptive qualitative approach with a case study method, focusing on ethical mechanisms, institutional role dynamics, and the challenges faced by the Badan Kehormatan in carrying out its duties. Data were obtained through in-depth interviews with members of the Badan Kehormatan, DPRD members, and secretariat staff, as well as official documents related to the code of conduct and internal regulations. The findings reveal that the role of the Badan Kehormatan emphasizes moral, educational, and interpersonal approaches rather than formal-procedural enforcement. The ethical mechanisms applied are informal and adaptive but are not yet supported by a strong institutional framework. Major challenges include weak sanction regulations, the political positioning of Badan Kehormatan members, and the absence of a strong ethical culture within the DPRD. This study concludes that ethical enforcement requires the strengthening of values, institutional structures, and consistent political role models. Based on the research findings, the researchers recommend several measures, including strengthening ethical mechanisms through written SOPs, enhancing institutional capacity and ethical education at the Serang City DPRD Ethics Council, and reforming attendance regulations and institutional transparency of DPRD ethical performance. Furthermore, suggestions for future research include expanding the study context, using a qualitative-narrative or phenomenological approach, and utilizing participatory instruments such as focus group discussions (FGD) or participant observation.